EVALUATION OF THE EFFECTIVENESS OF MANAGEMENT AT THE NORTH CHINA UNIVERSITY OF TECHNOLOGY IN BEIJING - KMECOVA, Iveta (Trends in education, 2016)
Quality education is the greatest asset for the individual and allows him to successfully integrate into the practical life. Evaluation of the quality of education is therefore justified. Within the paper I present partial results of surveys aimed at identifying the views of staff and students on the quality of the course management. The aim was to determine the attitude and view of teachers, where they see options for the modernization and innovation learning process, as well as to determine student attitudes and opinions towards the level of motivation, motivational techniques, teaching methods, textbooks. The aim was to obtain feedback from the students' perspective. The study was conducted at NCUT in Beijing, China. The conclusion consists of practice recommendations to improve motivation.
Keywords: quality of educational process; effeciency of educational process; education; didactic means; motivational methods; teaching methods; teacher; student.